Rancang Bangun Sistem Informasi Tahanan dan Barang Bukti Menggunakan Model Prototype Pada Kepolisian Daerah Jambi - Qintari, Tisya; Suratno, Tri; Mauladi, Mauladi (Prodi Sistem Informasi FST Universitas Jambi, 2019)
The process of administering detainees and evidence managed by the Directorate of Detention and Evidence in the Jambi Regional Police which is currently underway is considered to be less effective and efficient because there are still some shortcomings that could have an impact in the future. These deficiencies can interfere with the administrative process of detainees and evidence that should run optimally in the future. Therefore this research was conducted to provide solutions to these problems by developing a new information system that can overcome and deal with the various shortcomings that occur today. The information system development method used in this study is design and creation using the prototype method. The prototype method consists of 5 stages: communication, quick plan, modeling quick design, contruction of prototype and deployment, delivery and feedback. In addition, the system that has been built will be functionally tested using black box testing. This test is conducted as a trial method that focuses on finding input conditions errors in the system. The results of the study using black box testing using 55 points of the test scenario show that this system is functionally running optimally